Iron Rims as an Imaging Biomarker in MS: A Systematic Mapping Review - Amjad I. AlTokhis; Abdulmajeed M. AlOtaibi; Ghadah A. Felmban; Cris S. Constantinescu; Nikos Evangelou (Diagnostics, 2020)
Background: Multiple sclerosis (MS) is an autoimmune, inflammatory, demyelinating and degenerative disease of the central nervous system (CNS). To date, there is no definitive imaging biomarker for diagnosing MS. The current diagnostic criteria are mainly based on clinical relapses supported by the presence of white matter lesions (WMLs) on MRI. However, misdiagnosis of MS is still a significant clinical problem. The paramagnetic, iron rims (IRs) around white matter lesions have been proposed to be an imaging biomarker in MS. This study aimed to carry out a systematic mapping review to explore the detection of iron rim lesions (IRLs), on clinical MR scans, and describe the characteristics of IRLs presence in MS versus other MS-mimic disorders. Methods: Publications from 2001 on IRs lesions were reviewed in three databases: PubMed, Web of Science and Embase. From the initial result set 718 publications, a final total of 38 papers were selected. Results: The study revealed an increasing interest in iron/paramagnetic rims lesions studies. IRs were more frequently found in periventricular regions and appear to be absent in MS-mimics. Conclusions IR is proposed as a promising imaging biomarker for MS.